An integrated hydro-economic modelling framework to evaluate water allocation strategies II: scenario assessment - George, B.A.; Malano, H.M.M.; Davidson, B.; Hellegers, Petra J.G.J.; Bharati, Luna; Massuel, S. (Elsevier, 2011)
In this paper the results of an assessment of the hydrological and economic implications of reallocating water in the Musi sub-basin, a catchment within the Krishna Basin in India, are reported. Policy makers identified a number of different but plausible scenarios that could apply in the sub-basin, involving; supplying additional urban demand from agricultural allocations of water, implementing a number of demand management strategies, changing the timing of releases for hydropower generation, changing the crops grown under irrigation, reducing existing stream flows and allowing for more environmental flows. The framework chosen to undertake this assessment was a simulation model that measures and compares the economic values of water allocation scenarios determined from a water allocation model that accounts for supplies of groundwater and surface water across a number of regions and over a variety of uses. Policy makers are provided with the range of measures on the security of the supply of water and the social costs and benefits of reallocating water between sectors and across regions within the sub-basin. Taking water from agriculture to supply urban users has a greater impact on irrigation supplies during dry years. It was also found that changing the allocation of water between sectors, by taking it away from agriculture had a large positive economic impact on the urban sector. Yet the costs involved in undertaking such a strategy results in a significant loss in the net present value of the scheme. Stream flow reductions, if significantly large (at around 20%), were found to have a large physical and economic impact on the agricultural sector. Implementing water saving strategies in Hyderabad was found to be more cost effective than taking water from agriculture, if rainwater tanks are used to achieve this. Changing the timing of hydropower flows resulted in best meeting of irrigation demand in NSLC and NSRC. Under this scenario, the crops grown under irrigation were found to have a significant economic impact on the sub-basin, but not as large as farmers undertaking crop diversification strategies, ones which result in farmers growing less rice. The security of supplying water to different agricultural zones has significantly improved under this scenario. Finally, releasing water for environmental purposes was found to have only a minor impact on the agricultural sector.